Hydrogel-encapsulated extracellular vesicles for the regeneration of spinal cord injury - Nazerian, Yasaman; Nazerian, Amirhossein; Mohamadi-Jahani, Fereshteh; Sodeifi, Parastoo; Jafarian, Maryam; Javadi, Seyed Amir Hossein (Frontiers in Neuroscience, 2023)
Spinal cord injury (SCI) is a critical neurological condition that may impair motor, sensory, and autonomous functions. At the cellular level, inflammation, impairment of axonal regeneration, and neuronal death are responsible for SCI-related complications. Regarding the high mortality and morbidity rates associated with SCI, there is a need for effective treatment. Despite advances in SCI repair, an optimal treatment for complete recovery after SCI has not been found so far. Therefore, an effective strategy is needed to promote neuronal regeneration and repair after SCI. In recent years, regenerative treatments have become a potential option for achieving improved functional recovery after SCI by promoting the growth of new neurons, protecting surviving neurons, and preventing additional damage to the spinal cord. Transplantation of cells and cells-derived Extracellular vesicles (EVs) can be effective for SCI recovery. However, there are some limitations and challenges related to cell-based strategies. Ethical concerns and limited efficacy due to the low survival rate, immune rejection, and tumor formation are limitations of cell-based therapies. Using EVs is a helpful strategy to overcome these limitations. It should be considered that short half-life, poor accumulation, rapid This is a provisional file, not the final typeset article clearance, and difficulty in targeting specific tissues are limitations of EVs-based therapies. Hydrogelencapsulated exosomes have overcome these limitations by enhancing the efficacy of exosomes through maintaining their bioactivity, protecting EVs from rapid clearance, and facilitating the sustained release of EVs at the target site. These hydrogel-encapsulated EVs can promote neuroregeneration through improving functional recovery, reducing inflammation, and enhancing neuronal regeneration after SCI. This review aims to provide an overview of the current research status, challenges, and future clinical opportunities of hydrogel-encapsulated EVs in the treatment of SCI.